2013
DOI: 10.1016/j.jmoldx.2013.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Circulating miRNA Biomarkers for Predicting Lymph Node Metastasis in Gastric Cancer

Abstract: We validated candidate biomarkers using circulating miRNAs by analyzing serum miRNA concentrations from patients with gastric cancer (GC) to predict lymph node (LN) metastasis. In a pilot study, serum levels of miR-21, miR-27a, miR-106b, miR-146a, miR-148a, miR-223, and miR-433 were compared in 10 healthy donors, 16 LN-positive patients with GC, and 15 LN-negative patients with GC. Then, we compared the level of three miRNAs (miR-21, miR-146a, and miR-148a) with the total of 79 GC patients with or without LN m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(54 citation statements)
references
References 34 publications
2
52
0
Order By: Relevance
“…In contrast to mRNAs and proteins, miRNAs are not involved in complex post-transcriptional and post-transcriptional modification. Considering the limitations of condition and time for tissue sampling (Freidin et al 2012), circulating miRNAs are optimal prog- nostic biomarkers for cancer (Sanfiorenzo et al 2013;Chen et al 2013b;Lin et al 2013;Greenberg et al 2013;Kim et al 2013). However, further studies should be conducted before miRNA can be extensively used in clinical applications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to mRNAs and proteins, miRNAs are not involved in complex post-transcriptional and post-transcriptional modification. Considering the limitations of condition and time for tissue sampling (Freidin et al 2012), circulating miRNAs are optimal prog- nostic biomarkers for cancer (Sanfiorenzo et al 2013;Chen et al 2013b;Lin et al 2013;Greenberg et al 2013;Kim et al 2013). However, further studies should be conducted before miRNA can be extensively used in clinical applications.…”
Section: Discussionmentioning
confidence: 99%
“…The unique expression profile of circulating miRNA may function as the fingerprint of different diseases because miRNAs are highly stable in serum and plasma (Chen et al 2008). Circulating miRNA has been considered as a potential non-invasive biomarker in tumor diagnosis and prognosis (Sanfiorenzo et al 2013;Chen et al 2013b;Lin et al 2013;Greenberg et al 2013;Kim et al 2013;Rani et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the roles of certain SNPs in the miRNA-coding regions and their effects on the risk of human gastric cancers have been extensively investigated (22). It has been demonstrated that SNPs in miRNA-coding regions are associated with gastric carcinogenesis and increased susceptibility to the development of gastric cancer (23,24). Better understanding of the association between these SNPS and the risk of gastric cancer may provide novel insights into the prevention and early diagnosis of human gastric cancer in high-risk populations and important guidelines for the management of this malignancy (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several reports have highlighted the diagnostic and prognostic utility of serum or plasma-based miRNA levels, because tumorderived miRNAs are present in human circulation in remarkably stable forms that are protected from endogenous ribonuclease activity [5]. These studies suggest that serum or plasma miRNA-based assays may constitute accurate methods for the diagnosis and prognostic prediction of cancer, although, to date, only a few studies have specifically focused on the clinical significance of circulating miRNAs in patients with GC [6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%